Tagus River microbial profile through nanopore sequencing on samples gathered from Prainha do Braco de Prata, Lisbon [version 3; peer review: 1 approved, 2 approved with reservations] - Mariana Pestana; Cristiano Pedroso-Roussado; Mónica Nunes; Ricardo Dias; Marcelo Pereira; Pedro Pascoal; Nuno Nunes (Open Research Europe)
Background Freshwater ecosystems play a vital role for hosting life, and their study can elucidate their dynamic state throughout time. However, there is not much knowledge about the microbial profiles and their relevance for the ecosystem balance is still unclear. Methods In this Brief Report three freshwater samples collected in the Tagus River north margin were analysed through 16S-targeted nanopore sequencing and by customized bioinformatics pipeline. Results Our results revealed a consensual microbial profile with Candidatus Pelagibacter, Egibacter, and Ralstonia as the most abundant genera. Additionally, through a literature review we found that the ecosystem services provided by these genera are mostly related to organic matter decomposition. Conclusions Despite the need for a more robust sampling and analyses, we conclude that there is potential to use microbial profile approaches to help define the relevant microbial biomarkers to clarify the ecosystem services in the Tagus River freshwater ecosystem.